Prevalence and correlates of suicidal ideation in the general public during the fifth wave of COVID-19 pandemic in Hong Kong - Lo, Heidi Ka Ying; Chan, Joe Kwun Nam; Wong, Corine Sau Man; Wong, Gabbie Hou Sem; Lei, Janet Hiu Ching; So, Yuen Kiu; Fung, Vivian Shi Cheng; Chu, Ryan Sai Ting; Ling, Rachel; Chung, Albert Kar Kin; Lee, Krystal Chi Kei; Cheng, Calvin Pak Wing; et al. (Frontiers in Psychiatry, 2024)
Introduction Literature reveals increased suicidal ideation in the general population during pandemic. However, few COVID-19 studies comprehensively assessed factors associated with suicidal ideation, and mixed findings were observed. We aimed to examine prevalence and correlates of suicidal ideation in general public during the peak of fifth COVID-19 wave in Hong Kong based on a broad array of relevant measures. Methods This survey assessed 14,709 community-dwelling adults during March 15–April 3, 2022. Comprehensive assessment was administered including socio-demographics, pre-existing mental/physical morbidity, mental-health symptoms, resilience, loneliness, coping strategies, and pandemic-related factors. Presence of suicidal ideation was evaluated by ratings of item 9 on Patient-Health-Questionnaire-9. Results A total of 2,249 (15.3%) participants exhibited suicidal ideation. Multivariable-regression analysis found that being single and unemployed, pre-existing mental disorder, more severe depressive and anxiety symptoms, higher levels of loneliness and engagement in avoidant coping were significantly associated with suicidal ideation. Conversely, attaining tertiary educational level or above, greater resilience and adopting problem-focused coping were associated with lower likelihood of suicidal ideation. Although univariate-analyses revealed that a number of pandemic-related factors were linked to suicidal ideation, none remained significant in the multivariable model. Conclusion A significant proportion of people experienced suicidal ideation during the peak of fifth COVID-19 wave. Risk and protective factors identified would facilitate early identification of high-risk individuals and provision of targeted interventions to minimize suicidal ideation and risk of self-harm. Caution should be exercised due to study limitations of a cross-sectional design which precluded establishing causality among variables, and reliance on self-reported data.